Nocturnal awakenings of Brazilian immigrants in Massachusetts - Paixão, Talita Monsores; Teixeira, Liliane Reis; Cozendey-Silva, Eliana Napoleão; Siqueira, Carlos Eduardo Gomes (Sleep Science, 2021)
Objective The purpose of this study was to assess the relationship between the quantity of jobs and nocturnal awakenings of Brazilians living in Massachusetts.Material and Methods We sampled of 48 documented Brazilians around the age of 45.5 years old. 52.1% of them were women. Data gathering occurred for three weeks, using the Pittsburgh Sleep Quality Index. Participants also wore wrist actigraph and filled sleep/wake diary for a week.Results The sleep quality of immigrants with one job (mean=8.58, SD=4.16) is better when compared to immigrants with 2-3 jobs (mean=12.7, SD=3.57) according to the PSQI scores. Immigrants with 2-3 jobs reported dissatisfaction on three components of the scale: sleep duration, sleep efficiency and sleep quality.Discussion There is a positive relationship between the quantity of jobs and nocturnal awakenings and between nocturnal awakenings and complaints related to sleep apnea among Brazilians in Massachusetts. The assessment of systemic morbidities associated with sleep pattern changes should be considered in future research.
Keywords: Brazilian Immigrants; Work; Sleep; Sleep Wake Disorders; Sleep Apnea Syndrome; Sleepiness